Biomonitoring of aquatic habitat using Apodu Dam in Malete, Moro local government area of Kwara state Nigeria as a case study - Akanbi-Gada Mariam Abiola; Owoleke Veronica Amina; Oluwatobi AS; Abdul-Majeed Oyejimi Oyeleke (Annals of Marine Science - Peertechz Publications, 2023)
Water bodies such as dams are an essential part of the ecosystems and the Apodu dam, a Local Government Area of Kwara State supplies water for the populace of Malete. The water is used for both domestic and agricultural purposes. Given the proposed rural development in the catchment area of the Apodu dam, it becomes imperative therefore to do extensive biomonitoring of the dam before the development begins so as to determine the likely source of pollution in the dam as well as determine the health of the dam. Ten samples of both water and plants were collected at different sampling points designated as A-J. The samples collected were digested and analyzed using standard techniques. Data generated from the research were subjected to T-test to determine whether there is a significant variation in the two sets of data. The parameters examined fall within the permissible level of standards set by the Federal Environmental Protection Agency (FEPA) and the World Health Organisation (WHO). Total hardness (TH) was 88.00-128.80 mg/l, pH 6.60-6.80, Total dissolved solids (TDSS) 242.00-420.00 mg/l, Electrical conductivity 102.32-103.39 µs cm, Biological Oxygen Demand (BOD) 3.47-3.53 mg/l, Chemical Oxygen Demand (COD) 104.00-168.00 mg/l and Dissolved oxygen (DO) 3.47- 3.53 mg/l. The lower concentration of DO is an indication of high water quality and this is advantageous for aquatic life as it suggests that there is less decomposition of foreign materials. In conclusion, high potential for an increasingly detrimental impact on the water quality resulting from increased anthropogenic activities especially if the proposed developments commence is imminent.